Solving Boston’s Traffic Nightmare While Reducing Transportation Sector Emissions: The Case for Bus Rapid Transit and Congestion Pricing Along I-93’s Southeast Expressway. - Palumbo, Matthew R. (Tufts Archival Research Center, 2018)
Submitted in partial fulfillment of the degree Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Abstract: Solving Boston’s Traffic Nightmare While Reducing Transportation Sector Emissions: The Case for Bus Rapid Transit and Congestion Pricing Along I-93’s Southeast Expressway